Pengembangan UMKM Berbasis ekonomi Kreatif dalam Meningkatkan Ekonomi Berkelanjutan Di Kota Medan - Eltrina Naibaho; Monang Juanda Tua Sihombing (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to examine the development of creative economy-based Micro, Small, and Medium Enterprises (MSMEs) in promoting sustainable economic growth in Medan City. Furthermore, it seeks to identify the supporting and inhibiting factors encountered by creative economy-based MSME entrepreneurs in developing their businesses. This research employed a descriptive qualitative approach. The primary data were obtained from MSMEs operating in the food and beverage sector in Medan City. Data were collected through observation, in-depth interviews, and documentation. The collected data were analyzed using qualitative data analysis techniques, including data reduction, data display, and conclusion drawing. The findings reveal that creative economy-based MSMEs implement various marketing development strategies, particularly through personal selling and continuous promotional activities via social media conducted by both business owners and employees. In addition, these enterprises strive to achieve their sales targets by increasing production capacity, introducing product variations, expanding their target markets, and enhancing customer service quality. However, the study also identifies several factors that hinder the development of MSMEs, including limited resource capabilities and inadequate managerial competencies. These constraints significantly affect business growth and sustainability. Consequently, MSME owners experiencing such challenges must continuously adapt and improve their business management practices to maintain business resilience and ensure long-term sustainability.